Endogenous climate coalitions and free trade: Building the missing link - Thomas Kuhn; Radomir Pestow; Anja Zenker (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2018)
In this paper, we discuss the endogenous formation of climate coalitions in an issue-linkage regime. In particular, we propose to build a link to the issue of preferential free trade. Trade privileges exclusively granted to members of the climate coalition work as an incentive mechanism for countries to join in. A multi-stage strategic trade framework is used in which coalition (fringe) countries can dispose of a policy set comprising a discriminatory import-tariff on dirty goods as well as producer emission permits traded on a common (local) permits market. A fairly novel modelling of the preferential free trade area is incorporated which is at the core of our approach. We find strong support for the claim that trade liberalization can promote relatively large and effective climate coalitions compared to the single issue regime. As a policy implication, negotiations on international climate treaties and free trade arrangements should be interlinked.
Keywords: Q54; Q56; F18; F15; Q58; 330; Climate Change; International Environmental Agreements; Free Trade; Issue Linkage; Emission Permits